Laboratory Evaluation of Egg White and Milk External Biomarkers for Wasmannia auropunctata (Hymenoptera: Formicidae). Issue 6 (12th December 2019) - Montgomery, Michelle; Hagler, James R; Vanderwoude, Casper; Lynch, A Jasmyn J; Robinson, Wayne A
Abstract: Acquisition and retention of two protein markers were tested on little fire ants, Wasmannia auropunctata Roger. Pure (100%) cow's milk and a dilution (10%) of chicken egg whites were applied to W. auropunctata directly by contact spray plus residue or indirectly via residual contact only with protein-marked plant debris. Protein-marked ants were held in plastic shoe-box-sized containers, collected at 0, 24, and 48 h after exposure to their respective marks, and then examined for the presence of the marks by a chicken egg albumin and milk casein-specific enzyme-linked immunosorbent assay. Cross-contamination rates were assessed by allowing ants marked with egg whites to interact with an equal number marked milk for 24 and 48 h, and then collected either individually or in bulk. Results indicated that the egg white biomarker was retained longer than milk and that more ants were successfully marked when the direct spray application method was employed. Cross-contamination rates were highest among bulk-collected ants and lowest among ants collected individually after 24 h. However, the rates of cross-contamination among individually collected ants increased and were similar to that of bulk-collected ants after 48 h. On the basis of our results, external protein marking may not be suitable if mass trapping is required or if the study extends beyond 24 h due to high cross-contamination rates among specimens collected in bulk and reduced marker detection rates.